2015
DOI: 10.1371/journal.pone.0138029
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Receptor-1 Selective Agonist Enhances Collateral Growth and Protects against Subsequent Stroke

Abstract: Background and PurposeCollateral growth after acute occlusion of an intracranial artery is triggered by increasing shear stress in preexisting collateral pathways. Recently, sphingosine-1-phosphate receptor-1 (S1PR1) on endothelial cells was reported to be essential in sensing fluid shear stress. Here, we evaluated the expression of S1PR1 in the hypoperfused mouse brain and investigated the effect of a selective S1PR1 agonist on leptomeningeal collateral growth and subsequent ischemic damage after focal ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
(74 reference statements)
0
11
0
1
Order By: Relevance
“…Two specific metabolite or metabolite classes that require further investigation are sphinganine-1-phosphate (4-fold higher in naïve ob/ob mice) metabolites and the metabolite class of plasmalogens. The sphinganine-1-phosphate-related metabolite sphingosine-1-phosphate has been implicated in poor outcome for ischemic stroke ( Ichijo et al, 2015 ; Maceyka et al, 2013 ; Moon et al, 2015 ) and sphingolipid metabolism before and after stroke is therefore worthy of investigation. Plasmalogens are identifiable by their ether linkage at the sn-1 position, and can make up 20% of all glycerophosphocholines in the brain ( Farooqui and Horrocks, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two specific metabolite or metabolite classes that require further investigation are sphinganine-1-phosphate (4-fold higher in naïve ob/ob mice) metabolites and the metabolite class of plasmalogens. The sphinganine-1-phosphate-related metabolite sphingosine-1-phosphate has been implicated in poor outcome for ischemic stroke ( Ichijo et al, 2015 ; Maceyka et al, 2013 ; Moon et al, 2015 ) and sphingolipid metabolism before and after stroke is therefore worthy of investigation. Plasmalogens are identifiable by their ether linkage at the sn-1 position, and can make up 20% of all glycerophosphocholines in the brain ( Farooqui and Horrocks, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that the amount of S1PR1 mRNA peaked at 6 h after blood vessel occlusion, and this was significantly higher than in control mice. Similarly, in a previous report utilizing a mouse cerebral infarction model, Ichijo described that the S1PR1 mRNA levels peaked 7 days after blood vessel occlusion [ 22 ]. We also investigated the immunohistochemical co-staining of CD31 and S1PR1 in retinal flat mounts.…”
Section: Discussionmentioning
confidence: 61%
“…Ichijo and Iwasawa et al. described how shear stress applied to occluded blood vessels led to the formation of collateral vessels in their experimental cerebral infarction model [ 15 , 22 , 23 ]. Similarly, Lloyd et al.…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type and Ttpa -/- mice were fed on a normal (36 mg of α-tocopherol/kg), α-tocopherol-supplemented (600 mg of α-tocopherol/kg), or α-tocopherol-deficient diet until the time of use. For the ischemic mouse model, male C57Bl/6 (18 weeks old) mice were used for the surgical procedure for left permanent middle cerebral artery occlusion [ 20 ] and used for the histological examinations on day 7 after surgery. For the traumatic brain injury model, postnatal day 2 (P2) mice were subjected to cryogenic injury as described previously [ 21 ].…”
Section: Methodsmentioning
confidence: 99%